The Factor Structure of the Arabized ‎Jordanian Version of the Frost ‎Multidimensional Perfectionism Scale-Brief ‎‎(FMPS-B) ‎ - Al-Shayeb, Abdelhafez (Jordan Journal of Educational Sciences, 2024)
The current study aimed to investigate the factor structure of the Arabized Jordanian version of the Frost Multidimensional Perfectionism Scale-Brief (FMPS-B’s) and its psychometric properties. Data for this study were collected from 362undergraduate male and female students from a public Jordanian university. The results of the exploratory factor analysis revealed that two subfactors were extracted,perfectionistic concerns, and perfectionistic strivings with good reliability coefficients. This was confirmed by comparing the fit indicators of two models, the two-factor model and the bi-factor model using the confirmatory factor analysis method, where it was found that the two-factor model fit the data well, while the bi-factor model does not. Convergent validity of the scale was also investigated through examining the relationship between the scores on each subfactor with anxiety and depression, where it was revealed that the perfectionistic concerns subfactor is significantly correlated with anxiety as well as depression, while the perfectionistic strivings subfactor is correlated with anxiety only